Simon the Composite Sorcerer - Eastman, David L. (2022)
Simon Magus is a key figure in the earliest apocryphal Acts of Peter. He is a sorcerer and confidant of the emperor who clashes with Peter and, in later apocryphal texts, with both Peter and Paul. However, this is not simply the villain of the Acts of the Apostles. In this article I will argue that the apocryphal Simon is a composite figure drawn substantially, but not necessarily wholly, from the Simon of Acts 8 and the Elymas/Bar-Jesus figure who opposes Paul in Acts 13.
Keywords: Acts of the Apostles; Elymas; Simon Magus; Apocryphal Acts; Apostle Paul; Apostle Peter